Snoring and incident chronic kidney disease: a community-based prospective cohort study - Changhyun Lee; Young Su Joo; Sangmi Lee; Shinchan Kang; Joohwan Kim; Ki Heon Nam; Hae-Ryong Yun; Jong Hyun Jhee; Hyoungnae Kim; Seung Hyeok Han; Tae-Hyun Yoo; Shin-Wook Kang; et al. (BMJ Open)
Objectives Previous studies have shown that symptoms of sleep-disordered breathing are associated with metabolic derangements and vascular disease development. However, the relationship between snoring and renal function is not well investigated. The association between snoring and the development of incident chronic kidney disease (CKD) in subjects with normal renal function was evaluated.Design Prospective cohort study.Setting Ansung (rural community) and Ansan (urban community) cities.Participants Community-based cohort participants aged 40–69 years.Methods A total of 9062 participants in the Ansung–Ansan cohort study were prospectively followed up from 2001 to 2014. The participants were classified into three groups: non-snorer, <1 day/week and ≥1 day/week. The main outcome was incident CKD, which was defined as an estimated glomerular filtration rate of <60 mL/min/1.73 m2 during the follow-up period.Primary outcome Incident CKD.Results The mean subject age was 52.0±8.9 years, and 4372 (48.2%) subjects were male. The non-snorer,<1 day/week and ≥1 day/week groups included 3493 (38.5%), 3749 (41.4%), and 1820 (20.1%) subjects, respectively. Metabolic syndrome was more prevalent in the snoring groups than in the non-snoring group. Snoring frequency showed a significant positive relationship with age, waist:hip ratio, fasting glucose, total cholesterol (Tchol) and low-density lipoprotein cholesterol. During a mean follow-up of 8.9 years, 764 (8.4%) subjects developed CKD. Cox proportional hazards model analysis revealed that the risk of CKD development was significantly higher in subjects who snored ≥1 day/week than in non-snorers, even after adjustments for confounding factors (HR 1.23, 95% CI 1.09 to 1.38, p<0.01).Conclusion Snoring may increase the risk of CKD development in subjects with normal renal function.